Relevance of sol–gel transition and spinodal decomposition for hierarchical porosity structure of monolithic alumina - Passos, Aline R. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Springer Nature, 2021)
In situ techniques were used to investigate the hierarchical porous structure of alumina monoliths formed by the combined processes of sol–gel transition and spinodal phase separation. The addition of low molecular weight poly(ethylene oxide) (PEO) in the sol–gel reaction of aluminum chloride induced phase separation between aluminate gel and PEO solvent. In situ time-resolved small-angle X-ray scattering (SAXS) measurements revealed that structural evolution during gelation of a sample without PEO was dominated by Ostwald ripening. With PEO addition, this coarsening mechanism, occurring during a short intermediate stage (6 min), was followed by the aggregative coalescence of phase separating domains during the late stage of spinodal decomposition. The effect of PEO in the gelation mechanism also influenced the porous structure formed by calcination of the alumina monoliths. During calcination for PEO removal and conversion from xerogel to ceramic, in situ SAXS monitoring evidenced that the formation of mesopores followed the spinodal decomposition mechanism proposed by Cahn’s theory. Alumina with well-defined meso- and macropore families, high specific pore volume (2.0 cm3 g−1), and high surface area (252 m2 g−1) was obtained as a result of spinodal decomposition during the sol–gel transition followed by heat treatment. [Figure not available: see fulltext.]
Keywords: Alumina; In situ SAXS; Sol–gel; Spinodal decomposition